Stormwater detention reservoirs: An opportunity for monitoring and a potential site to prevent the spread of urban microplastics - Moruzzi, Rodrigo Braga [UNESP]; Speranza, Lais Galileu [UNESP]; da Conceição, Fabiano Tomazini [UNESP]; de Souza Martins, Suely Teodoro [UNESP]; Busquets, Rosa; Campos, Luiza Cintra (MDPI, 2020)
Stormwater runoff carries pollutants from urban areas to rivers and has the potential to be a main contributing source of microplastics (MPs) to the ecosystem. Stormwater detention reservoirs (SDRs) differ from ponds and lakes in that SDRs retain most particulate matter and they are emptied after storm events. This paper investigates the occurrence of MPs in the SDR of the Alto-Tiete catchment area, Itaim stream in Poa city, Sao Paulo, Brazil. The MPs found were classified in different categories: shapes (fragment, line/fibre, film/sheet and pellet); size (<0.5 mm, between 0.5 mm and 1 mm and >1 mm); and polymer composition. Results have shown that most of the MPs found in the samples are fragments (57%), followed by pellets (27%), fibres/lines (9%), and then films/sheets (6%). Small particles (<0.5 mm) represented 89% of the total MPs, and this category mainly included fragments (62%) and pellets (30%). MPs were found in a vast variety of shapes and colours, which shows a likely variety of sources. Besides the occurrence of MPs in the stormwater samples, the potential of SDRs as a first sanitary barrier to retain MPs before they reach the ecosystem has been speculated.
Keywords: Microplastics; Runoff; Sediments; Stormwater detention reservoir; Urban water